2009
DOI: 10.1111/j.1468-2982.2009.01895.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pain sensitivity of the scalp in patients with nummular headache: A cartographic study

Abstract: Nummular headache (NH) is characterized by focal pain fixed within a small round or elliptical area of the head surface. Sensory dysfunction is apparently restricted to the symptomatic area, but a thorough analysis of cranial pain sensitivity has not been performed. Pressure pain sensitivity maps were constructed for 21 patients with NH and 21 matched healthy controls. In each subject pressure pain thresholds (PPT) were measured on 21 points distributed over the scalp. In each patient PPT were also measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 38 publications
7
41
0
Order By: Relevance
“…Eight of our patients (two in BREF and six in FREF groups) had a nummular type head pain in the stemming area between EF paroxysms, as it has been previously described [3, 14]. EF and NH probably share a peripheral source in their pathogenesis [15]. …”
Section: Discussionsupporting
confidence: 59%
“…Eight of our patients (two in BREF and six in FREF groups) had a nummular type head pain in the stemming area between EF paroxysms, as it has been previously described [3, 14]. EF and NH probably share a peripheral source in their pathogenesis [15]. …”
Section: Discussionsupporting
confidence: 59%
“…These studies revealed that mechanical sensitivity depicted by assessing pressure pain thresholds (PPTs) is not uniformly distributed around the same muscle (Fern andez-delas-Peñas et al, 2008;Ge et al, 2008) or around an anatomical area, e.g., the elbow (Ruiz_Ruiz et al, 2011), the hand (Fern andez-de-las- Peñas et al, 2010b) or the head (Cuadrado et al, 2010). Furthermore, increased mechanical sensitivity can also occur on the nonaffected side as a sign of central sensitization .…”
Section: Introductionmentioning
confidence: 95%
“…A number of studies have proposed the utility of topographical pain sensitivity maps as an exploratory method allowing spatial assessment of sensitization mechanisms in several chronic pain disorders, e.g., lateral epicondylalgia (Ruiz_Ruiz et al, 2011), carpal tunnel syndrome (Fern andez-de-las-Peñas et al, 2010b), headaches Cuadrado et al, 2010), migraine (Fern andez-de-las-Peñas et al, 2009, 2010a, shoulder pain or work-related musculoskeletal disorders (Binderup et al, 2011). These studies revealed that mechanical sensitivity depicted by assessing pressure pain thresholds (PPTs) is not uniformly distributed around the same muscle (Fern andez-delas-Peñas et al, 2008;Ge et al, 2008) or around an anatomical area, e.g., the elbow (Ruiz_Ruiz et al, 2011), the hand (Fern andez-de-las- Peñas et al, 2010b) or the head (Cuadrado et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In NH, the painful area is generally located at the parietal area which is innervated by the ophthalmic branch of trigeminal nerve. A consistent location, size and shape [1,2], as well as allodynia and focal paresthesia [3,5] and trophic change [3,4], of the painful area rationally point to an involvement of the terminal endings in the epicranial tissue in NH. Since autoimmune disorders can cause sensory distal neuropathy, NH can be explained as a form of autoimmune-mediated epicranial painful neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is categorized as a primary headache in the International Classification of Headache Disorders, second edition [2]. NH is proposed a form of peripheral neuralgia of the trigeminal nerve [3] which is supported by the consistency of pain pattern, focal atrophic change [4], and local sensory alteration [5] within the painful area. Although intracranial secondaries [6][7][8] and previous focal trauma [9] have been found in a few NH patients, the etiopathogenesis of NH is factually unknown.…”
Section: Introductionmentioning
confidence: 99%